2007
DOI: 10.1007/s00420-007-0197-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dermal absorption and protective effectiveness of respirators for xylene in spray painters

Abstract: The present study showed that inhalation of solvent vapors in workers decreased as a result of wearing respirators and dermal exposure became the main contributor to the total body burden of solvents. Because workers had different attitude and behavior to wear respirators, the measured workplace protection factors varied. It is therefore equally important to prevent from being exposed to solvents through skin for shipyard spray painters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Interestingly, a study by Siebel and da Silva did not discover a significant difference in developing micronucleus among workers who had been wearing protective masks and those who had not; however, it found a decrease in the inhalation of genotoxic chemicals in those wearing masks. Their finding corroborates that of Chang et al who suggested a decrease in inhaling genotoxic chemicals in workers wearing masks (Chang et al, 2007;Siebel and da Silva, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, a study by Siebel and da Silva did not discover a significant difference in developing micronucleus among workers who had been wearing protective masks and those who had not; however, it found a decrease in the inhalation of genotoxic chemicals in those wearing masks. Their finding corroborates that of Chang et al who suggested a decrease in inhaling genotoxic chemicals in workers wearing masks (Chang et al, 2007;Siebel and da Silva, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Half of the workers reported to wear only masks while working. Chang et al (2007a) showed that painters wearing protective masks significantly reduced inhalation of two genotoxic substances: xylene by 96% and ethyl benzene by 94%. In our study, however, no differences were found in the number of MN between workers who reported to wear protective masks and those who did not adopt such protective measure.…”
Section: Discussionmentioning
confidence: 99%
“…Although much is known about exposures that can lead to OCD, there is no existing job-exposure matrix for dermatitis-specific exposures. However, many exposures cause both asthma and contact dermatitis 19–21. The Occupational Asthma-specific Job Exposure Matrix (OAsJEM) identifies job groups with exposure to compounds that are known to cause occupational asthma 22 23.…”
Section: Introductionmentioning
confidence: 99%